2002
DOI: 10.1097/00002060-200203000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Injection vs. Nonsteroidal Antiinflammatory Drug and Splinting in Carpal Tunnel Syndrome

Abstract: Both splinting combined with the use of a nonsteroidal antiinflammatory drug and steroid injection into the carpal tunnel resulted in significant improvement in carpal tunnel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
11

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 13 publications
3
40
0
11
Order By: Relevance
“…Celiker et al 13 in a prospective study compared oral anti-inflammatory plus splinting (neutral wrist, nocturnal use) to corticosteroid injection with methylprednisone acetate. Patients who had thenar muscle atrophy were not included in the study; so, perhaps, the assumption can be made that the study population of 33 hands in 23 subjects had mild or moderate CTS.…”
Section: Cortisone Injectionmentioning
confidence: 99%
“…Celiker et al 13 in a prospective study compared oral anti-inflammatory plus splinting (neutral wrist, nocturnal use) to corticosteroid injection with methylprednisone acetate. Patients who had thenar muscle atrophy were not included in the study; so, perhaps, the assumption can be made that the study population of 33 hands in 23 subjects had mild or moderate CTS.…”
Section: Cortisone Injectionmentioning
confidence: 99%
“…Celiker et al conducted an unblinded randomized clinical trial with an 8-week follow-up of 33 hands in 23 patients, comparing the efficacy of steroid injection against splinting combined with the use of a non-steroidal anti-inflammatory drug. 25 It showed that both treatment regimes resulted in significant improvement but there was no difference between the two interventions. These findings resonate with those from ours.…”
Section: Discussionmentioning
confidence: 98%
“…Carpal tunnel syndrome is the most commonly treated compression neuropathy and continues to be controversial in both diagnosis and treatment (17)(18)(19). The prevalence of carpal tunnel syndrome has been reported to be as high as 2.7% in the general population (20).…”
Section: Discussionmentioning
confidence: 99%